Non-Civil Servant Muzakkī Intentions in Paying Zakāh in BAZNAS of Sidoarjo and Trenggalek Regency, East Java - Asegaf, M. Maulana; Muchlisin, Muchammad Chafidz (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2023)
This study aims to explore the intentions of non-civil servant (non-ASN) Muzakkī in paying zakāh through BAZNAS in Sidoarjo and Trenggalek Regencies, East Java, using the Theory of Planned Behavior (TPB) as an analytical framework. Through a qualitative-descriptive approach, primary data were obtained via structured interviews with BAZNAS officials and selected non-ASN zakāh payers. The findings reveal that among the three core TPB components—attitude toward behavior, subjective norms, and perceived behavioral control—attitude emerges as the most influential determinant of zakāh intention. While social pressure (subjective norms) and access convenience (perceived control) played a secondary role, these factors became pivotal in shaping the decision to channel zakāh through formal institutions like BAZNAS. The study highlights that institutional strategies such as transparency, community engagement, and digital accessibility significantly impact zakāh compliance among private-sector contributors. This research offers a practical contribution to zakāh management literature by contextualizing behavioral intention theories in faith-based philanthropy. It also identifies institutional gaps and proposes actionable strategies for zakāh authorities globally, especially in countries with decentralized zakāh systems. Future studies should expand this behavioral framework to other Muslim-majority regions, enabling comparative insights into zakāh compliance and institutional trust across socio-religious contexts.